The Divining Snake: Reading Genesis 3 in the Context of Mesopotamian Ophiomancy - Smith, Duane E. (Journal of Biblical literature, 2015)
This article argues that the snake in Gen 3 is best understood within a cultural context that included Mesopotamian ophiomancy. Reading the snake in Gen 3 in this context leads to understanding Hebrew טוב ורע as meaning “good fortune and ill fortune.” The article reviews ophiomancy as reflected in omen series Šumma Ālu ina mēlê šakin and other Mesopotamian omen and ritual texts. Of the hundreds of snake omens, forty some deal with the ominous behavior of snakes acting in the presence of a man and a woman. These omens provide instructive parallels for the interaction of the snake in Gen 3 and the first couple. They also provide evidence for the cultural context of the snake’s role as a communicator of YHWH’s mind if not YHWH’s will. With several well-attested examples of polysemy and alliteration in Gen 2–3, ancient authors and readers no doubt perceived an unstated relationship between (“snake”) and (“divination”). Hebrew טוב and רע have overlapping semantic ranges with Akkadian damqu and lemuttu. Good fortune and ill fortune are within those overlapping ranges. Scholars have long noted parallels between Gen 2–3 and other Mesopotamian traditions, most notably Gilgamesh and Adapa.